Pemanfaatan Buah Pinus Sebagai Bio-briket dalam Mendukung Capacity Building Pemuda Desa Pationgi - Riska, Andi; Muhammad Irfan Taufan Asfar, A.; Muhamad Iqbal Akbar Asfar, A.; Safar, Muh.; Yulita; Hasmariyanti; Nurannisa, A. (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2023)
Pinecone waste has been a crucial problem for rubber farmers in Pationgi Village, Patimpeng District, Bone Regency. Various methods have been used by partners to overcome the collection of fruit waste, starting from making holes for waste and burning it bit by bit. But this adds to the problem because it causes widespread forest fires and causes air pollution. Therefore, in implementing the community service student creativity program, it is carried out to assist partners in transforming pinecone waste into bio briquettes through three main stages in the implementation of this community service namely Tudang Sipulung (Counseling), Sipakario- Rio (Training) and Siaseddingeng (Assistance) which is a term that is familiar to partners to hear. The results obtained show an increase in knowledge and capacity building of partners regarding the utilization of pinecone waste into bio-briquettes with an increase of 90%, for partners' ability to utilize pinecone waste reaching 85%. Increased partners are able to build skilled souls and instill the entrepreneurial spirit of partners and make bio-briquettes a wood substitute fuel.